Performance evaluation of a secure Low Level Reader Protocol (LLRP) connection - Qadir, Sana; Siddiqi, Mohammad Umar (IJCSNS, 2009)
The recently ratified Low Level Reader Protocol (LLRP) specifies the interaction between a RFID Reader and Client. It has been of much interest in the RFID community but adoption is being stalled by its lack of formal scrutiny especially with regard to its security. This paper surveys the work that has been undertaken on this protocol, assesses its security vulnerabilities and examines possible security solutions. It then presents the design and implementation of LLRP endpoints that use Transport Layer Security (TLS) to setup a secure LLRP connection. Based on previous performance studies, appropriate metrics are selected to indicate the performance of the resulting TLS-LLRP connection. Specifically, the overhead of securing a LLRP connection using TLS is quantified and a detailed analysis of the results is undertaken to determine the TLS cipher suites and parameters that provide the best compromise between the level of security and performance.